Proton beam versus photon beam dose to the heart and left anterior descending artery for left-sided breast cancer. (July 2015) - Lin, Lilie L.; Vennarini, Sabina; Dimofte, Andreea; Ravanelli, Daniele; Shillington, Katie; Batra, Sonny; Tochner, Zelig; Both, Stefan; Freedman, Gary
Abstract Purpose. The purpose of this study was to compare the dose to heart, left anterior descending (LAD) artery and lung between proton and photon beam irradiation for left-sided early stage breast cancer. Material and methods. Ten women with early stage left-sided breast cancer were treated with breast conserving surgery and radiation. Whole breast radiation was delivered for actual treatment via a tangential technique with deep inspiration breath hold (DIBH) utilizing inverse planned intensity-modulated radiation therapy (IMRT). Each patient was replanned on an Institutional Review Board (IRB)-approved prospective study using en face proton beam radiation with both uniform scanning (US) and pencil beam scanning (PBS) techniques. Results. Both PBS (0.011 Gy) and US (0.009 Gy) proton plans resulted in a significantly lower mean heart dose compared to IMRT (1.612 Gy) (p < 0.05 for PBS vs. IMRT and US vs. IMRT). The Dmean, Dmin, Dmax, and D0.2cm3 of the LAD with either proton technique were significantly lower (p = 0.005) compared to IMRT. Both US and PBS reduced the mean dose to the lungs compared to IMRT. The coverage of the breast planning target volume was comparable between photon and proton plans. Conclusions. The dose to whole heart was relatively low in this study of patients treated under conditions of DIBH. However, proton beam radiation was associated with lower minimum, maximum, and dose to 0.2 cm3 of the LAD, which is the critical structure for late radiation therapy effects, compared to even the most optimized photon beam plan with DIBH and IMRT.